SISTEM KEAMANAN PENGUNCIAN SEPEDA MOTOR DENGAN AUTENTIKASI WIFI SMARTPHONE - Muhajirin, Muhajirin; Taufik; Arafah, Muhammad; Angriawan, Randy; Ilham; Pasnur; Maslihatin, Tatik; Halid, Agus; Sabri, Muhammad (STMIK KHARISMA Makassar, 2025)
Motorcycle theft continues to rise in various regions, highlighting the need for more reliable security systems. Conventional protection methods, such as double locks or standard alarms, have proven to be vulnerable and insufficient. This research aims to design and implement a motorcycle security system based on WiFi MAC address authentication from the owner's smartphone. The system is built using the ESP8266 microcontroller, which scans nearby devices and matches their MAC addresses against a pre-registered list. If a match is found, the vehicle is allowed to start. In addition to authentication, the system is equipped with a vibration sensor to detect suspicious activity when the motorcycle is in an OFF state. Test results indicate that the system can effectively distinguish between authorized and unauthorized devices, and responds accurately and promptly under various test conditions